ANALISIS BUTIR SOAL UJIAN SEMESTER GENAP MATA PELAJARAN KIMIA KELAS X IPA SMA PGRI PEKANBARU TAHUN AJARAN 2013/2014 - Yonelia, Vemi Yonelia Vemi; Haryati, Sri Haryati Sri; Johni A, Johni A Johni A (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Evaluation is one of the component parts that holds a very important role in learning system. One evaluation conducted is evaluation students learning result. The evaluation students learning result generally ranked students on normal curve, so that most of the students are or approaching the median (KKM), as well as a small portion is above the average and below the average. Information was obtained from high school PGRI Pekanbaru, even semester examination results grade X IPA on chemical subjects classified was not ranked students on a normal curve. There are 69 students who reach scores of above KKM and only 1 students under KKM. The KKM score is 80 for students to get completeness . Until in fact the exam result curve was obtained a curve right set. So it needs to be done analysis grains of question which has been used on that examination. Analysis grains of question was done as qualitative and quantitative analysis. The result of the qualitative analysis of the 40 questions, there was only 10 questions (25% ) satisfied aspect of the material, the aspect of the construction and language. The propotion of the division on each chapter not balanced and the distribution of the domain of cognitive taxonomic Bloom has not spread equally. Results of the quantitative analysis of 40 questions, there was 1 questions (2,5%) with a category acceptable, 15 questions (37,5%) with categories is fixed and 24 questions (60%) were rejected by category. Key words: analysis grain of questions, quality, quantity